ISOLASI AMILASE DARI KECAMBAH BIJI NANGKA (Artocarpus heterophyllus Lam) - Fahmi, Ismi; Astuti, Winni; Sitorus, Saibun (Jurusan Kimia FMIPA UNMUL, 2017)
This research aims to isolate the crude extract amylase of sprouted seeds jackfruit (Artocarpus heterophyllus Lam) and determine the specific activity. Determination of total protein concentration and amylase activity of enzyme crude extract on seed germination jackfruit (Artocarpus heterophyllus Lam). Determination of total protein concentration using the method of Bradford, whereas the determination of amylase activity was performed using dinitrosalisilat acid method (DNS). The results showed a total protein concentration of the enzyme crude extract of sprout seeds jackfruit (Artocarpus heterophyllus Lam) is 319,47 ug / mL, amylase activity of 13,96 U / mL and specific activity is 1748,05 U / mg.